Gasdermin D mutation protects against renal ischemia reperfusion injury - Jennifer S. Y. Li; Aadhar Moudgil; Daniel N. Meijles; Karli Shaw; Sohel M. Julovi; Katie Trinh; Stephen I. Alexander; Natasha M. Rogers (Physiological Reports)
Abstract Pyroptosis, the most inflammatory form of cell death, is dependent on membrane pore formation governed by the assembly of cleaved Gasdermin D (GSDMD). We hypothesized that regulated necrosis pathways are crucial in the pathophysiology of acute kidney injury (AKI). Mice with an isoleucine‐to‐asparagine loss‐of‐function mutation in the Gasdermin D gene (GSDMDI105N/I105N) generated by ethylnitrosourea‐mutagenesis were subjected to bilateral renal ischemia–reperfusion injury (IRI) with bio‐molecular readouts performed at 24 h. IRI was also performed in mice pretreated with disulfiram. Whole‐body irradiation followed by syngeneic bone marrow transplantation generated chimeric mice prior to IRI. Mice homozygous for the GSDMD I105N mutation were protected from IRI, demonstrating lower serum creatinine and reduced histological injury, as well as decreased pro‐inflammatory cytokine expression and oxidative stress. Chimeric mice showed that this protection was predominantly governed by mutations in the parenchymal tissue, with a potential contribution from the hematopoietic compartment. Pharmacological inhibition of GSDMD pore formation using disulfiram protected against IRI. Manipulation of GSDMD is an attractive target to mitigate inflammation and cellular death following AKI.